Sonographic studies of external jugular vein and common carotid artery in Sahiwal calves - Rathi, Abhishek; Kumar, Gulshan; Purohit, Sanjay; Pandey, R.P. (Indian Journal of Veterinary Surgery, 2026)
The objective of the study was to perform sonographic evaluation of the external jugular vein (EJV) and common carotid artery (CCA) in the neck of healthy Sahiwal calves and to study their echo-biometric parameters. Eighteen calves used in the study were divided into three groups of six animals each based on the age group: group I (0-4 months), group II (> 4 and up to 8 months) and group III (> 8 and up to 12 months). B-mode and Doppler ultrasound scanning were done in standing position in all the animals without sedation, using multi-frequency transducer. The CCA appeared as an anechoic structure of uniform diameter in longitudinal scan, with a thicker wall in transverse scan; the three layers- intima, media, and adventitia were easily discerned. The walls of the EJV appeared as thin hyperechoic lines with a clear demarcation from the surrounding tissue. Various sonographic parameters such as diameter of vessel (D), skin to vessel distance (S), peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI) and resistivity index (RI) were recorded wherever possible. For CCA, the S was found significantly greater in group III, whereas the PSV and EDV showed a general increasing trend with age. For EJV, the D was significantly greater in group III and velocity showed a general increasing trend with age. is most suitable for scanning In conclusion, the external jugular vein and common carotid artery in Sahiwal calves can be reliably scanned at the mid ventro-lateral aspect of the neck. Doppler evaluation can be performed in standing calves with minimal restraint, using maximum neck extension for the common carotid artery and normal neck extension for the external jugular vein.